Growth and Shocks: Evidence from Rural Ethiopia. - Dercon, S (2004)
Using panel data from rural Ethiopia, the article discusses the determinants of consumption growth (1989-1997), based on a microgrowth model, controlling for heterogeneity. Consumption grew substantially, but with diverse experiences across villages and individuals. Rainfall shocks have a substantial impact on consumption growth, which persists for many years. There also is a persistent growth impact from the large-scale famine in the 1980s, as well as substantial externalities from road infrastructure. The persistent effects of rainfall shocks and the famine crisis imply that welfare losses due to the lack of insurance and protection measures are well beyond the welfare cost of short-term consumption fluctuations.